Hypoxia/Reoxygenation Effects on Ion Transport across Rat Colonic Epithelium - Schindele, Sabine; Pouokam, Ervice; Diener, Martin (Frontiers in Physiology, 2016)
Ischemia causes severe damage in the gastrointestinal tract. Therefore it is interesting to study how the barrier and transport functions of intestinal epithelium change under hypoxia and subsequent reoxygenation. For this purpose we simulated hypoxia and reoxygenation on mucosa-submucosa preparations from rat distal colon in Ussing chambers and on isolated crypts. Hypoxia (N2 gassing for 15 min) induced a triphasic change in short-circuit current (Isc): a transient decrease, an increase and finally a long-lasting fall below the initial baseline. During the subsequent reoxygenation phase, Isc slightly rose to values above the initial baseline. Tissue conductance (Gt) showed a biphasic increase during both the hypoxia and the reoxygenation phases. Omission of Cl- or preincubation of the tissue with transport inhibitors revealed that the observed changes in Isc represented changes in Cl- secretion. The radical scavenger trolox C reduced the Isc response during hypoxia, but failed to prevent the rise of Isc during reoxygenation. All changes in Isc were Ca2+-dependent. Fura-2 experiments at loaded isolated colonic crypts revealed a slow increase of the cytosolic Ca2+ concentration during hypoxia and the reoxygenation phase, mainly caused by an influx of extracellular Ca2+. Surprisingly, no changes could be detected in the fluorescence of the superoxide anion-sensitive dye mitosox or the thiol-sensitive dye thiol tracker, suggesting a relative high capacity of the colonic epithelium (with its low O2 partial pressure even under physiological conditions) to deal with enhanced radical production during hypoxia/reoxygenation.